Fiscal Responsibility Legal Framework—New Paradigm for Fiscal Discipline in the EU - Mihaela Tofan; Mihaela Onofrei; Anca-Florentina Vatamanu (Risks, 2020)
This paper aims at studying the legal aspects of the European Union (EU)’s fiscal policy, analyzing the statute of fiscal responsibility legal framework, the different measures undertaken in the last years with respect to European trends in fiscal governance and their implications for challenges in public finance sustainability. The research started from the presupposition that there is a lack of mechanisms capable of enforcing the area of public finance sustainability, and the implication of the events that created the economic conjuncture of recent years reveals that the solidity of public finances has reached an impasse and needs to be enhanced. The analyzed documents from the area of fiscal responsibility show formal respect for the legislative framework aimed at consolidating public finance sustainability and accentuate the need to use fiscal laws, independent institutions and mechanisms that put constraints on policymakers and determine them to spend more efficiently, invest more wisely, and obtain better results regarding public finance sustainability. We conclude that future policymaking processes need to consider the consolidation of independent fiscal institutions founded by Fiscal Responsibility Law framework, completed by fiscal rules and, therefore, need to redesign the fiscal risk management process.